BTS ARMY’s #BTSLOVEYOURSELF: A Worldwide K-Pop Fandom Participatory Culture in Twitter - Saraswati, Listya Ayu; Nurbaity (Lililacs Journal, 2021)
Korean popular music (K-pop) fandom is under spotlight as the K-pop industry has rapidly grown transnationally. Fandom practices across nation borders in social media has grown out from supporting their idols by buying the records, continuously discussing idols’ personal life, and attending live music concerts, to supporting social causes in the name of the idols. This paper investigates fandom participatory culture of creating and supporting social activism message in social media. By collecting and analyzing a large-scale of fandom activity data from Twitter, we investigate to what extent fandom participatory culture is prevalent and important in transnationalism of K-pop, in particularly social activism in social media. By analyzing the Twitter data of ARMY on #BTSLOVEYOURSELF, we show the participatory culture is what gives the fandom and their messages bigger effect in social media which is beyond the idol’s industrial well-made representation and image. However, there is also a possibility of inter-cultural intermediaries of fandom practices to echo idol’s message in social media and to define success for the multi-billions industry.